A revision of distribution, ecology and conservation issues of the threatened comb-claw beetle Gerandryus aetnensis (Coleoptera: Tenebrionidae, Alleculinae) - Piccini, Irene; Cristiano, Luca; Di Pietro, Viviana; Bonelli, Simona; Biscaccianti, Alessandro B. (Fragmenta entomologica, 2021)
Gerandryus aetnensis (Rottenberg, 1871) is a rare and localized beetle, previously known only for Maritime Alps and Sicily. In this paper we provide a revision of geonemy, ecology and status of conservation, including a proposal for a new assessment of its extinction risk in the framework of the European saproxylic beetles, based upon several new records from western Alps, northern, central, southern Apen- nine, and Sicily. Thus, the species is a W-Alpino-Apenninic subendemic saproxylic species, associated to tree hollows in both coniferous and deciduous forests. We also propose to assess G. aetnensis as Vulnerable at global and Italian level.